Diet and physical activity interventions do have effects on body composition and metabolic syndrome parameters in overweight and obese adolescents and their mothers - Nişancı Kılınç, Fatma; Çağdaş, Deniz N (The Turkish Journal of Pediatrics, 2013)
To determine the effects of lifestyle intervention and diet on body composition, anthropometric measurements, and metabolic syndrome (MS) in obese and overweight adolescents and their mothers, a diet and lifestyle intervention program was administered for 16 weeks to 19 9-17-year-old (12.52 ± 2.85 years) adolescents (female/male, 8/11) with a body mass index (BMI) value over the 90th percentile; hemoglobin (Hb)A1C, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), fibrinogen, and C-reactive protein levels of the adolescents and anthropometric measurements of the mothers were compared. In some of the anthropometric values (body weight (BW), BMI, waist circumference (WC), skinfold thicknesses, body fat tissue, and lean tissue mass), a statistically significant difference was observed in pre- and post-application measurements (p